Commensal Neisseria kill Neisseria gonorrhoeae through a DNA-dependent mechanism in mice - Kim, Won Jong (Cell Host Microbe, 2019)
The mucosa is colonized with commensal Neisseria. Some of these niches are sites of infection for the STD pathogen Neisseria gonorrhoeae (Ngo). Given the antagonistic behavior of commensal bacteria towards their pathogenic relatives, we hypothesized that commensal Neisseria may negatively affect Ngo colonization. Here, we report that commensal species of Neisseria kill Ngo through a mechanism based on genetic competence and DNA methylation state. Specifically, commensal-triggered killing occurs when the pathogen takes up commensal DNA that contains a methylation pattern it does not recognize. Indeed, any DNA will kill Ngo if it can enter the cell, is differentially methylated, and has homology to the pathogen genome. Consistent with these findings, commensal Neisseria elongata accelerates Ngo clearance from the mouse in a DNA uptake-dependent manner. Collectively, we propose that commensal Neisseria antagonizes Ngo infection through a DNA-mediated mechanism, and that DNA is a potential microbicide against this highly drug resistant pathogen.